BIOACTIVE CONSTITUENTS AND ANTIOXIDANT EFFICACY OF AURICULARIA POLYTRICHA - B, Packialakshmi; G, Sudha; M, Charumathy (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Objective: Auricularia polytricha is a most popular edible and medicinal fungus in China and other Asian countries because of its high nutritional value and good taste. The objective of this study was to evaluate the antioxidant potency, total phenol, and flavonoid content in the hot water extract of A. polytricha fruiting bodies. Methods: The antioxidant property was investigated using various in vitro chemical and biological models such as 2, 2'-azino-bis [3-ethylbenzothiazoline6-sulfonicacid], dimethyl-4-phenylenediamine radical scavenging assay, cupric reducing antioxidant capacity assay, phosphomolybdenum reducing antioxidant power assay, Î²-carotene bleaching and lipid peroxidation inhibition assays. Results: A. polytricha exhibited antioxidant activity in a dose-dependent manner with lower EC values in all scavenging assays. A considerable amount of secondary metabolites such as phenol and flavonoids were observed in the extract. 50 Conclusion: The results demonstrated that A. polytricha has a potential significance for seeking new natural antioxidant agents against oxidative stress. Keywords: Î²-carotene bleaching, Free radicals scavenging, Lipid peroxidation, Total phenols, Total flavonoids, Wood ear mushrooms.